Literature Study of the Effectiveness of Picture Story Media in Teaching Speaking Skills for Elementary School Students: Studi Literatur Efektifitas Media Cerita Bergambar Dalam Mengajarkan Keterampilan Berbicara Siswa Sekolah Dasar - Fita Alfiatul; Machful Indra Kurniawan (Academia Open, 2022)
This study aims to determine the results of research on the effectiveness of illustrated story media in improving the speaking skills of elementary school students. The background of this research is to describe and want to know the effectiveness of illustrated story media to teach speaking skills to students in elementary schools. This research uses literature study research. The data obtained by the research are journals, reports, articles, and relevant documents that are in accordance with the problems studied. Based on the results of the data analysis conducted by the researchers, a result was obtained, namely the illustrated story media is an effective medium to teach speaking skills possessed by students in elementary schools. With the media picture story, students can improve their speaking skills.